Oxidative Stress in Cognitive and Epigenetic Aging: A Retrospective Glance - Kandlur, Aditi; Satyamoorthy, Kapaettu; Gangadharan, Gireesh (Frontiers in Molecular Neuroscience, 2020)
Brain aging is the critical and common factor among several neurodegenerative disorders and dementia. Cellular, biochemical and molecular studies have shown intimate links between oxidative stress and cognitive dysfunction during aging and age-associated neuronal diseases. Brain aging is accompanied by oxidative damage of nuclear as well as mitochondrial DNA, and diminished repair. Recent studies have reported epigenetic alterations during aging of the brain which involves Reactive Oxygen Species (ROS) that regulates various systems through distinct mechanisms. However, there are studies which depict differing roles of reactive oxidant species as a major factor during aging. In this review, we describe the evidence to show how oxidative stress is intricately linked to age-associated cognitive decline. The review will primarily focus on implications of age- associated oxidative damage on learning and memory, and the cellular events, with special emphasis on associated epigenetic machinery. A comprehensive understanding of these mechanisms may provide a perspective on the development of potential therapeutic targets within the oxidative system.